Quantenstochastik: 15.12. bis 21.12.1991 - Waldenfels, Wilhelm von; Accardi, Luigi (Tagungsbericht, 1991)
Luigi Accardi; Robert Alicki; David Applebaum; Stephane Attal; Alberto Barchielli; Vjacheslav P. Belavkin; Andreas Boukas; Marek Bozejko; Carlo Cecchini; Alexandr Chebotarev; Ken I. Dykema; Moritz Epple; Franco Fagnola; Mark Fannes; Wolfgang Freudenberg; P. Gibilisco; H. Hasegawa; Fumio Hiai; Takeyuki Hida; Alexander S. Holevo; Thomas Hudetz; Robin L. Hudson; Patrick D.F. Ion; Palle E.T. Jorgensen; D. Koroliuk; Burkhard Kümmerer; J. Martin Lindsay; Lu Yun-Gang; Hans Maassen; Shahn Majid; Masanori Ohya; Kalyanapuram R. Parthasarathy; Adam Paszkiewicz; Denes Petz; Slawomir Rudnicki; Jean-Luc Sauvageot; Michael Schürmann; Kalyan B. Sinha; Michael Skeide; Roland Speicher; Andre F.M. Verbeure; Dan Voiculescu; Wilhelm von Waldenfels; Noboru Watanabe; Reinhard F. Werner